Mesoscopic Mapping of Stimulus-Selective Response Plasticity in the Visual Pathways Modulated by the Cholinergic System - Laliberté, Guillaume; Othman, Rahmeh; Vaucher, Elvire (Frontiers in Neural Circuits, 2020)
The cholinergic potentiation of visual conditioning enhances visual acuity and discrimination of the trained stimulus. To determine if this also induces long-term plastic changes on cortical maps and connectivity in the visual cortex and higher associative areas, mesoscopic calcium imaging was performed in head-fixed awake GCaMP6s adult mice before and after conditioning. The conditioned stimulus (0.03 cpd, 30°, 100% contrast, 1Hz-drifting gratings) was presented 10 min daily for a week. Saline or Donepezil (DPZ, 0.3 mg/kg, s.c.), a cholinesterase inhibitor that potentiates cholinergic transmission, were injected prior to each conditioning session and compared to a sham-conditioned group. Cortical maps of resting state and evoked response to the monocular presentation of conditioned or non-conditioned stimulus (30°, 50 and 75% contrast; 90°, 50, 75 and 100% contrast) were established. Amplitude, duration, and latency of the peak response, as well as size of activation were measured in the primary visual cortex (V1), secondary visual areas (AL, A, AM, PM, LM, RL), retrosplenial cortex (RSC), and higher cortical areas. Visual stimulation increased calcium signaling in all primary and secondary visual areas, the RSC, but no other cortices. There were no significant effects of sham-conditioning or conditioning alone, but DPZ treatment during conditioning significantly decreased the integrated neuronal activity of superficial layers evoked by the conditioned stimulus in V1, AL, PM, and LM. The activity of downstream cortical areas was not changed. The size of the activated area was decreased in V1 and PM, and the signal-to-noise ratio was decreased in AL and PM. Interestingly, signal correlation was seen only between V1, the ventral visual pathway, and the RSC, and was decreased by DPZ administration. The resting state activity was slightly correlated and rarely affected by treatments, except between binocular and monocular V1 in both hemispheres. In conclusion, cholinergic potentiation of visual conditioning induced change in visual processing in the superficial cortical layers. This effect might be a key mechanism in the establishment of the fine cortical tuning in response to the conditioned visual stimulus.